A new species of Eupariini from Eocene Baltic amber (Coleoptera: Scarabaeidae: Aphodiinae) - Tamutis, Vytautas; Alekseev, Vitalii I.; Bukejs, Andris (Zootaxa, 2017)
Based on 10 specimens from Late Eocene Baltic amber, an extinct species of Eupariini (Coleoptera: Scarabaeidae: Aphodiinae), Airapus lithuanicus Tamutis, Alekseev, & Bukejs new species, is described and illustrated. The new species is compared with two known fossil representatives of Aphodiinae from Baltic amber. The generic placement of these two species, Saprosites succini (Zang, 1905) and Ataenius europaeus Quiel, 1910, is discussed, as are details of paleoecology for the new species.